DNA barcoding: how many earthworm species are there in the south of West Siberia? - S. V. Shekhovtsov; N. E. Bazarova; D. I. Berman; N. A. Bulakhova; E. V. Golovanova; S. V. Konyaev; T. M. Krugova; I. I. Lyubechanskii; S. E. Peltek (Вавиловский журнал генетики и селекции)
Earthworms are a widespread and ecologically important group of animals, which has the highest total biomass in some ecosystems and often defines the composition of soil fauna. Earthworms are known to have high cryptic genetic diversity. In this study we attempted to estimate earthworm species diversity in the south of West Siberia by DNA barcoding. This method employs short fragments of the genome to identify species, and allows one to work with specimens that cannot be identified by conventional techniques, as well as to search for new species and predict their phylogenetic affinities. As the target sequence we took a fragment of the mitochondrial cytochrome oxidase 1 (cox1) gene. The studied territory (Novosibirsk and Tomsk oblasts, Altai krai, and the Altai Republic) is known to contain 16 species and subspecies of earthworms. We analyzed 259 individuals from twelve locations and detected 27 genetic clusters. Ten of them correspond to known species (A. caliginosa, E. fetida, O. tyrtaeum, D. r. tenuis, D. octaedra, E. balatonica, E. sibirica, as well as three genetic lineages of E. nordenskioldi nordenskioldi). Seventeen of the 27 clusters do not have close sequence similarity to any known earthworm species. Representatives of some of these novel clusters are morphologically similar to the Eisenia n. nordenskioldi/E. n. pallida species complex and may belong to new genetic lineages of this complex. The rest of the novel clusters probably represent new earthworm species. Therefore, we can conclude that a large portion of earthworm biodiversity in the south of West Siberia is still unexplored.